(untitled) (Research, Society and Development, 2022)
In current time, it is evident the necessity of animal welfare education policies. Animal welfare is defined as the state of an individual attempting to adjust to the environment and education material can encourage dialogue inside schools. We aimed to verify the presence or absence of animal welfare related content in school books and survey the perceptions of the students about the subject, associating with the socioeconomic profile of the school district and with the overall school performance in the SARESP test. This study was performed between July and November, with seven of the twenty-two public schools in the city of Araçatuba, São Paulo, Brazil. Seven books were collected for analysis from each school, totalizing 49 books, and 430 students answered a survey with 10 questions. The statistical analysis did not show relevant difference between biological gender, age, grade and socioeconomic profile and animal welfare knowledge perception. This study concluded that in most of the analyzed books, animal welfare topics are absent, and that there is no difference between the schools’ socioeconomic profile and animal welfare knowledge perception of the students.